The mastery of submission : inventions of masochism - Noyes, John K. (John Kenneth), 1955- (Cornell studies in the history of psychiatry., 1997)
Just over a hundred years ago, the Viennese physician Richard von Krafft-Ebing coined the term "masochism," after Leopold von Sacher-Masoch, who depicted pleasurable submission to cruelty in his novels. Noyes analyzes the social and political problems that inspired the concept, suggesting, for example, that the triumphant expansion of European colonialism was animated in part by an ambivalence in masculine sexuality. In a society of accelerating technological change and rampant social violence, the individual was believed to be rational and self-determined. Male masochistic behavior defied such a system of belief, placing women in dominance and using disciplinary technologies as instruments of sexual pleasure